Effects of the Change from Rate-of-Return to Price-Cap Regulation - Braeutigam, Ronald R.; Panzar, John C. (American Economic Review, 1993)
This article focuses on the use of incentive regulation in the telephone industry in the United States. We first characterize some of the difficulties that have led regulators to move away from traditional rate-ofreturn (cost-based) regulation and toward systems of regulation that provide incentives for increasingly efficient production, allowing firms to share in the social gains from efficiency with increased profits. We then discuss the basic structure of incentive regulation as it has most commonly been adopted in the telephone industry in the United States. The first is price-cap (PC) regulation, which typically allows the firm to